Catalogue of the Arabic, Persian and Turkish manuscripts in Belgium - Bauden, Frédéric. (Islamic Manuscripts and Books, 2016)
The Catalogue of the Arabic, Persian and Turkish Manuscripts in Belgium is a union catalogue aiming is to present the Oriental manuscripts held by various Belgian public institutions (Royal Library, university and public libraries). These collections and their contents are largely unknown to scholars due to the lack of published catalogues. This first volume, consisting of a bi-lingual (English and Arabic) handlist, concerns the collection of the Université de Liège, which holds the largest number of Oriental manuscripts (c. 500). Each title is briefly described, identifying the author and offering basic material information. Most of the manuscripts described in this handlist originate from North Africa.